Comprehensive study of Toxocara cati infection in stray cats at Al-Anbar province: Molecular detection and investigation vision - Alhayani, Omar; F Alshawi, Akil (The Iraqi Journal of Veterinary Medicine, 2024)
Cats are important hosts for different zoonotic including Toxocara, a group of ‎parasitic roundworms known as ascarid nematodes. This study aimed to analyse the ‎presence of T. ‎cati in stray cats in Al-Anbar province. Iraq This is first study of this ‎parasite in Al-Anbar province, which include the prevalence of T. ‎cati in stray ‎cats, as well as molecular study. This study was conducted on 50 stray cats, were examined ‎clinically, the signs were recorded for each animal, as well as the collection of faecal ‎samples to detect the eggs of parasite under microscope, and molecular examinations. ‎Blood samples also examined to know the effect of parasite on blood cells, especially the ‎eosinophils. Our results recognized the prevalence of infection was 48% when the ‎molecular method was used, and 40% when the microscopy method was used. Clinically, ‎the infected cats with signs were 4 (8%) from the total sick animals, as well as the same ‎percentage appeared in haematological examination (the eosinophilia). However, in Al-‎Anbar cities, T. cati is highly prevalent among stray cats. In order to eradicate the T. cati ‎parasite from the region’s stray cat population, efficient methods for doing so need to be ‎devised, and public education on animal and human health should also be stressed‎‎‎‎.